THE IMPACT OF CUSTOMER VALUE AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY AT WIJAYA MOTOR UNGARAN WORKSHOP - Mutiara Selvy; Edwin Zusrony; Tantik Sumarlin; Wesly Tumbur ML Tobing (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the effect of customer value and customer satisfaction on customer loyalty in the Gen Z and Millennial segments at the Wijaya Motor Workshop in Ungaran. The sample of this study consisted of 100 respondents selected using a non-random sampling method with a purposive sampling technique. Data collection used a questionnaire with a 5-point Likert scale measurement. The collected data were analyzed using multiple linear regression with the help of SPSS 29 software. The results of the study showed that the customer value variable and customer satisfaction variable partially had a significant effect on the customer loyalty variable. This finding indicates that increasing the value perceived by customers, as well as increasing the level of customer satisfaction, can significantly increase customer loyalty to the Wijaya Motor Workshop. The implication of this study is the importance of the Wijaya Motor Workshop to continue to increase customer value and satisfaction in order to maintain and increase customer loyalty, especially in the Gen Z and Millennial segments which are the focus of the study. Thus, the strategy of increasing customer value and satisfaction must be a top priority in efforts to develop workshop services and marketing.